ANALISIS FAKTOR YANG BERPENGARUH TERHADAP KEPATUHAN PASIEN HIPERTENSI DALAM MENJALANI PENATALAKSANAAN PENGOBATAN DI UPTD PUSKESMAS SUKAWATI II GIANYAR BALI - Ni Ketut Dian Erlyawati; Eka Diah Kartiningrum; Henry Sudiyanto; Rifaatul Laila Mahmudah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Hypertension is a degenerative disease that characterized by an increase in blood pressure over normal limits. Hypertension become the most common comorbid disease in cases of death due to Covid-19. Compliance with hypertension patients is needed in order to obtain a better quality of life for sufferers. This study aimed to determine the factors that influence the adherence in undergoing hypertension treatment management at the UPTD Puskesmas Sukawati II Gianyar Bali.This study used observational research with a crosssectional design. The variables studied included independent variables consisting of education, age, duration of suffering from hypertension, knowledge about hypertension, and family support. The dependent variable in this study was adherence in undergoing hypertension treatment management. The population in this study were all hypertensive patients as many as 757 people. The sample in this study were 88 hypertensive patients who fit the inclusion criteria who were selected using simple random sampling. The effect of education, age, duration of suffering from hypertension, knowledge about hypertension, and family support on patient adherence was analyzed using logistic regression and SEM.The results showed that there was an influence between education and age on adherence in undergoing hypertension treatment management in hypertensive patients (p value = 0.003), there was an influence between length of illness on adherence to undergoing treatment (pvalue = 0.043), there was an effect of knowledge about hypertension on adherence undergoing treatment management (pvalue=0.002), there is an effect of family support on adherence undergoing treatment management (pvalue=0.000), and family support is proven to be a mediator variable between education and knowledge of patient compliance in undergoing treatment management at the puskesmas (p value = 0.034 and 0.018).Patient education and knowledge about hypertension affect the support provided by the family and family support has a direct effect on patient adherence undergoing treatment management